Improving Winter Wheat Grain Yield and Water Use Efficiency through Fertilization and Mulch in the Loess Plateau. (1st November 2015) - Chen, Yanlong; Liu, Ting; Tian, Xiaohong; Wang, Xiaofeng; Chen, Huilin; Li, Meng; Wang, Shaoxia; Wang, Zhaohui
Abstract : Revealing the response of cereal yield and water use efficiency (WUE) to water management practices is crucial for achieving high and stable grain yields in drylands. A 3‐yr field study was conducted to develop a high‐yield, water‐saving cultivation strategy for winter wheat in the Loess Plateau of China. The study's treatments included (i) a control (CK), that is, no mulch or fertilizer, (ii) nitrogen and phosphorus fertilizers (NP), (iii) plastic film mulch plus fertilizers (NP+PF), (iv) straw mulch plus fertilizers (NP+S), and (v) plastic film combined with straw mulch plus fertilizers (NP+PF+S). The results indicated that, compared with CK, the NP treatment improved the grain yield (112%) and WUE (96%) of winter wheat but resulted in a 12% reduction in soil water storage after the jointing stage. With the NP+S treatment, there was no difference recorded in grain yield, yield components, or WUE of winter wheat (relative to the NP treatment). With the NP+PF treatment, there was a 53% increase in grain yield, a 46% increase in WUE, and a 21% increase in soil water storage after jointing compared to the NP treatment. The plastic film could also modify soil temperature, resulting in maximized soil water retention. Additionally, the NP+PF and NP+PF+S treatments resulted in similar results. Taking into account agricultural, environmental, and economic factors, in addition to optimal fertilization (NP), plastic film mulch is the recommended practice for maximum yield and water retention in tablelands, whereas plastic film combined with straw mulch is recommended in terraces.